The representation of betrayal and its impact on character development in barrer, ferrari, and pearson's transformers one script (2024) - Andre Leonard Marcyano Nunumete; Adeline Grace Marianne Litaay (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines the representation of interpersonal and institutional betrayal in the script of Transformers One (2024) and their impact on character development, using a psychological approach to literary criticism. Employing a qualitative descriptive method of textual analysis, the study treats the script as a literary text and draws its primary data from dialogue, narrative description, and character interaction. The analysis relies primarily on Harry T. Reis's theory of Perceived Partner Responsiveness, which interprets interpersonal betrayal through the components of understanding, validation, and caring, while Herbert Spencer's Social Organism Theory serves as a supporting framework for explaining institutional dysfunction. The findings show that interpersonal betrayal develops as the responsiveness cycle between Orion Pax and D-16 gradually collapses, transforming a bond of mutual trust into emotional invalidation and irreparable distrust. Institutional betrayal is represented through Sentinel Prime's abuse of authority, manifested in the confiscation of T-Cogs and the systematic falsification of Cybertronian history to exploit the mining class. These two forms of betrayal operate as a single, interconnected mechanism of psychological injury that produces divergent developmental outcomes: D-16's transformation into Megatron reflects radical identity dissolution and defensive self-reliance, while Orion Pax's transformation into Optimus Prime reflects moral consolidation and an expanded capacity for relational responsibility. The study concludes that betrayal functions in the script as a multi-layered psychological mechanism shaping identity, ideology, and leadership.